(untitled) (The Quintessential, 2025)
Magnetic Resonance Imaging (MRI) is an essential diagnostic tool in the modern world of healthcare; however, the use of MRI is accompanied by specific safety issues that require strict compliance with established guidelines. This study evaluated MRI safety standards in a few healthcare facilities located in Punjab, India, focusing on education, adherence to international and national guidelines, and readiness of the institution. The study employed a mixed-methods approach, which included surveys using quantitative data with health professionals from 78 facilities, as well as interviews with radiologists and facility managers. The results showed that, while the basic knowledge of MRI safety was prevalent among people, knowledge of specific guidelines like those of the Atomic Energy Regulatory Board (AERB) and the American College of Radiology (ACR) was minimal. In the area of infrastructure, there were gaps in the zoning system, signage, emergency preparedness, and the presence of specially trained MRI safety personnel. Qualitative analysis revealed concerns about inadequate staff training, lack of regular audits, and the absence of standardized procedures. The study highlights the urgent necessity of a well-structured policy, capacity-building programs, and regular institution audits. It suggests greater oversight of regulatory processes and synchronization with international standards for safety to improve MRI security within the region. These findings are part of the growing discussion about the safety of medical imaging in resource-constrained environments and provide practical recommendations for India's health policy.